Effect of antidepressant drug Flupentixol-Melitracen on locomotory behaviors of Drosophila (Journal of Bangladesh Academy of Sciences, 2025)
Antidepressant drugs are frequently used in the treatment of depression. Their effects on locomotory behavior have been poorly studied in human and Drosophila models. In this study, the effects of an antidepressant drug on larval crawling, negative geotaxis, and TOR gene expression were investigated in a Drosophila model. Drug-treated flies showed significantly higher activity in the negative geotaxis assay. However, no statistically significant differences were observed in the other behavioral assays or in TOR gene expression.J. Bangladesh Acad. Sci. 49(2); 295-298: December 2025